Deterioration of cement concrete floors under various aggressive industrial and chemical environments: an overview - Selvaraj, R.; Bhuvaneshwari, B. (Journal of Structural Engineering, 2025)
Cement concrete is one of the major construction materials used in almost all construction works in civil engineering from ordinary platform to mega structures. Less attention has been paid for the durability aspects of the structures and much has been paid for strength, stiffeners and ductility aspects in the design. It should be noted that the aggressiveness of the environment is growing everyday with the progressive nature of the development of the industries global wide and therefore the durability the concrete structures against these aggressive environment has become a global concern for the last few decades. In this paper, an attempt has been made to discuss the mechanisms involved in the deterioration of concrete in various vital industries such as food, fertilizer, paper and pulp, water supply, aircraft maintenance hangar, hospital and pharmaceutical, warehouses, live stock building industry and nuclear plants. The parameter involved for the deterioration of concrete are discussed and concluded that the transport of fluids in concrete has to be reduced drastically by improving the microstructure of the concrete for durable concrete.